2007
DOI: 10.1037/0012-1649.43.4.93
|View full text |Cite
|
Sign up to set email alerts
|

Normality and impairment following profound early institutional deprivation: A longitudinal follow-up into early adolescence.

Abstract: Longitudinal analyses on normal versus impaired functioning across 7 domains were conducted in children who had experienced profound institutional deprivation up to the age of 42 months and were adopted from Romania into U.K. families. Comparisons were made with noninstitutionalized children adopted from Romania and with nondeprived within-U.K. adoptees placed before the age of 6 months. Specifically, the validity of the assessment, the degree of continuity and change in levels of functioning from 6 to 11 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
176
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(194 citation statements)
references
References 69 publications
13
176
0
5
Order By: Relevance
“…On the other hand, the results of the present study are not compatible with some other studies on childhood adversities. In late childhood, emotional and behavioral disturbances were not clearly associated with early deprivation, in a group of early institutionalized Romanian adoptees (Colvert et al 2008;Kreppner et al 2007;Rutter et al 2001). Possibly, the children in this study were too young to measure particular sequelae.…”
Section: Trajectories Of Psychiatric Problems In Maltreated Childrenmentioning
confidence: 65%
See 1 more Smart Citation
“…On the other hand, the results of the present study are not compatible with some other studies on childhood adversities. In late childhood, emotional and behavioral disturbances were not clearly associated with early deprivation, in a group of early institutionalized Romanian adoptees (Colvert et al 2008;Kreppner et al 2007;Rutter et al 2001). Possibly, the children in this study were too young to measure particular sequelae.…”
Section: Trajectories Of Psychiatric Problems In Maltreated Childrenmentioning
confidence: 65%
“…Surprisingly, there was an increase in emotional and behavioral disturbances in the adopted group. However, there was no clear association between early deprivation and emotional or behavioral problems (Colvert et al 2008;Kreppner et al 2007;Rutter et al 2001). Furthermore, in a cross-sectional study of a non-adopted sample, Kessler et al (1997) found that the risk of psychiatric disorder onset was highest during the first few years after the occurrence of a childhood adversity.…”
mentioning
confidence: 98%
“…An extreme example of this is the plight of Romanian orphans (36). After neglect during the first six months since birth in state-run orphanages, these children have tended to become high cortisol reactors and to suffer profound social-emotional, as well as cognitive, developmental disturbances that persist at least into early adolescence (58). Romanian children orphaned later in life, or for briefer periods, tend to show less profound, and more easily reversible, developmental disturbances.…”
Section: Wwwannualreviewsorg • Gradients In Developmental Healthmentioning
confidence: 99%
“…[129][130][131][132] Meta-analytic findings and results from individual studies show at least partial benefits in cognitive and academic performance for institutionalized children adopted into high quality homes in the early years of life. 127,133 Attending high quality elementary schools, can promote academic achievement for children who did not attend preschool programs. 158 Validated programs to reduce learned helplessness or increase self-efficacy beliefs in children with poor academic achievement.…”
Section: Child Outcomes: Early Exposures or Interventions (Infancy-eamentioning
confidence: 99%